Feminist Afterlives Assemblage Memory in Activist Times - Chidgey, Red (Palgrave Macmillan Memory Studies, 2018)
This book interrogates why feminist memories matter. Feminist Afterlives explores how the images, ideas and feelings of past liberation struggles become freshly available and transmissible. In doing so, Red Chidgey examines how popular feminist memories travel as digital and material resources across protest, heritage, media, commercial and governmental sites, and in connection with the concerns and conditions of the present. Central case studies track repeated invocations to militant suffragettes and the We Can Do It! post-feminist icon over time and space. Assembling interviews, archival research and ethnographic accounts with provocative examples drawn from postfeminist media culture, a UNESCO heritage bid, protest at the London 2012 Olympic Games, and activist remembrance in zines and blogs, this is a broad-ranging study of 'restless' feminist pasts - both real and imagined. Richly researched and argued, this volume offers an original framework of 'assemblage memory' and sets out a new research agenda for the intersections between everyday activism, protest, and memory practices.